(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The lower molar of a large rodent collected near Terranuova Bracciolini in the Upper Valdarno Basin (Tuscany, Italy) and identified by Bosco (1899, 1900) as the beaver Trogontherium cuvieri Fischer, instead belongs to the porcupine Hystrix refossa Gervais. To date there is no evidence of the occurrence of the large beaver Trogontherium south of the Alps.